Evaluation of the efficacy and safety of percutaneous nephrolithotomy in children - Reddy, Madhusudhan; Annamalai, Arunkumar; Ali, Irshad; Sajja, Dheeraj Soma Siva; Devraj, Rahul; Reddy, Ram (International Surgery Journal, 2022)
Background: Children represent 2-4.3% of the total population of stone formers. Currently, the majority of stones in children can be managed either with shock-wave lithotripsy (SWL), percutaneous nephrolithotomy (PCNL), ureterorenoscopy (URS), or a combination of these modalities. Open surgery is currently necessary in a few selected cases only. In our study, we wanted to evaluate the overall results of pediatric percutaneous nephrolithotomy (PCNL). Methods: This study was based on patients of age <14 years who underwent PCNL at Nizam’s Institute of Medical Sciences, Hyderabad, India from January 2019 to December 2020. This was a retrospective study. Children with >1 cm calculi were included and the exclusion criteria were stones of <1 cm, deranged renal functions, and bleeding disorders. Results: We performed 73 PCNL procedures on 65 children, achieved complete stone clearance in 93% and residual calculi (<10 mm) was seen following five cases; three patients underwent redo-PCNL. The complication rate in the present study was (16.4%) however, 100% of the total complications were minor i.e. Clavien score I and II, which were managed conservatively. Conclusions: Thus, PCNL is a suitable treatment option for children with nephrolithiasis as avoiding open surgery in children. Higher rates of failure and numerous sessions under anesthesia with short wave lithotripsy (SWL) makes it a non-viable option in children. RIRS is not widely available, non-affordable by many and long-term outcomes not clearly known with respect to ureteral strictures in children.